The SoxRS response of Escherichia coli is directly activated by redox-cycling drugs rather than by superoxide - Gu, Mianzhi (2011)
When Escherichia coli is exposed to redox-cycling drugs, its SoxR transcription factor is activated by oxidation of its [2Fe–2S] cluster. In aerobic cells these drugs generate superoxide, and because superoxide dismutase (SOD) is a member of the SoxRS regulon, superoxide was initially thought to be the activator of SoxR. Its many-gene regulon was therefore believed to comprise a defense against superoxide stress. However, we found that abundant superoxide did not effectively activate SoxR in an SOD(−) mutant, that overproduced SOD could not suppress activation by redox-cycling drugs, and that redox-cycling drugs were able to activate SoxR in anaerobic cells as long as alternative respiratory acceptors were provided. Thus superoxide is not the signal that SoxR senses. Indeed, redox-cycling drugs directly oxidized the cluster of purified SoxR in vitro, while superoxide did not. Redox-cycling drugs are excreted by both bacteria and plants. Their toxicity does not require superoxide, as they poisoned E. coli under anaerobic conditions, in part by oxidizing dehydratase iron-sulfur clusters. Under these conditions SoxRS induction was protective. Thus it is physiologically appropriate that the SoxR protein directly senses redox-cycling drugs rather than superoxide.